Analisis Hukum Terhadap Implementasi Sistem Online Singel Submission (OSS) Dalam Perizinan Elektronik - Nugraha, Yudha Adi; Putri, Amelia; Azahra, Salsabila; Pittaloka, Intan Meylani; Matthew, Patricio Eduardo (DPPM Universitas Pelita Bangsa, 2025)
The implementation of the Online Single Submission (OSS) system aims to simplify business licensing procedures, enhance efficiency, and provide legal certainty. However, OSS implementation faces challenges, including regulatory disharmony, limited technological infrastructure, and low digital literacy. This study employs a normative juridical method with regulatory analysis, focusing on laws such as Law Number 11 of 2020 and Government Regulation Number 5 of 2021. The findings indicate that OSS effectively accelerates licensing processes through the Business Identification Number (NIB), but obstacles remain. To optimize the system, improvements in infrastructure, regulatory harmonization, and intensive education and outreach are necessary